Kesadaran Hukum Remaja di Wilayah Kepulauan dalam Menggunakan Media Sosial - Z. Zainuddin; Salle Salle (SIGn Jurnal Hukum, 2021)
This research aims to determine the legal awareness of juveniles in archipelagic areas using social media. This type of research is empirical legal research. The data was collected using a questionnaire and direct interviews. The data obtained in this research were then analyzed descriptively qualitatively with a sociological juridical approach to conclude the research's object. The results show that most of the legal awareness of juveniles in archipelagic areas is still low using social media. In this case, most juveniles do not know (54%) and do not understand (66%) on regulations for using social media. In addition, most behaviors of juveniles have violated (72%) of the regulations for using social media. Therefore, it is recommended for parents, teachers, and law enforcement officers to provide assistance and education to juveniles in using social media. In addition, law enforcement and local government officials can involve the participation of the community to be more intense in conducting legal counseling for juveniles. In this case, juveniles in archipelagic areas will have more legal awareness and comply with laws and regulations in the future.